Hubungan Sosialisasi Pengetahuan Remaja Putus Sekolah SLTA Tentang Paket C di PKBM Titian Amanah - Festi Dwi Rani; Wirdatul Aini; Syuraini Syuraini (Universitas Negeri Padang, 2018)
This research is motivated by the lack of knowledge of high school drop-out youth about Paket C in PKBMTitian Amanah. The purpose of this study is to describe: (1) socialization conducted by PKBM TitianAmanah, (2) knowledge of high school drop out teenagers about Paket C, and (3) relationship between socialization with knowledge of high school drop-out youth about Paket C. Population in this research 40 people and a sample of 30 people. With stratified random sampling sampling technique. Data collectiontechniques is a questionnaire and data collection tool is a questionnaire. Data analysis technique usingpercentage calculation and product moment correlation formula. The results of the study found that (1)the socialization conducted was not well implemented, (2) the knowledge of high school drop-out teens onPaket C is still unknown, and (3) there is a significant relationship between socialization with high schooldropout knowledge about Paket C in PKBM Titian Amanah.